Capacitive properties of hierarchically structured carbon nanofiber/graphene/MnO2 hybrid electrode with nitrogen and oxygen heteroatoms. (October 2016) - Lee, Do Geum; Kim, Yoong Ahm; Kim, Bo-Hye
Abstract: Hierarchically structured carbon nanofiber/graphene/MnO2 (CGMn) hybrid with oxygen and nitrogen functionalities was fabricated in the form of a web via electrospinning as an electrode material for supercapacitors. The CGMn electrode exhibited a high capacitance (225 Fg −1 at 1 mAcm −2 ), enhanced energy and power efficiency (15.8–13.6 Whkg −1 in the power density range of 197–4000 Wkg −1 ), and excellent capacitance retention (13% of the initial value at a discharge current of 20 mAcm −2 ) in a 6 M KOH aqueous electrolyte, because of the combination of the double-layer capacitance and the pseudocapacitive character associated with the surface redox-type reactions. The porosity and the number of heteroatoms of the CGMn composite were adjusted by changing the PMMA concentration and carbonization temperature. Therefore, the oxygen- and nitrogen-containing hierarchical porous CGMn hybrid prepared by a simple method is a promising candidate as an electrode material for supercapacitors.